2023
DOI: 10.26905/abdimas.v1i1.8060
|View full text |Cite
|
Sign up to set email alerts
|

Increasing reproductive health literacy among adolescent females in Islamic boarding schools through peer education

Abstract: The importance of reproductive health education in Islamic boarding schools is often overlooked. Whereas the prevalence of reproductive health issues among teenage females in Islamic boarding schools remains high, including anemia, vaginal discharge, dysmenorrhea, premenstrual syndrome, and personal hygiene. These difficulties have an impact such as absenteeism at school, wasting and infertility. Peer education is seen to be capable of addressing these issues since adolescents in Islamic boarding schools engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…Anemia education programs in Islamic boarding school and high school were not significant difference, as both of anemia education programs increased the knowledge among female students. In line with community service among adolescent females in Islamic boarding school Purwokerto that increasing reproductive health literacy was found after peer education (Nafisah et al, 2023). This is also in line with a randomized control study in India that a significant improvement of knowledge was found after intervention (Sharma & Rani, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Anemia education programs in Islamic boarding school and high school were not significant difference, as both of anemia education programs increased the knowledge among female students. In line with community service among adolescent females in Islamic boarding school Purwokerto that increasing reproductive health literacy was found after peer education (Nafisah et al, 2023). This is also in line with a randomized control study in India that a significant improvement of knowledge was found after intervention (Sharma & Rani, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Anemia education programs in Islamic boarding schools and high schools show no significant differences because both programs can improve female students' knowledge. Consistent with community services among adolescent females in Islamic boarding schools in Purwokerto, an increase in reproductive health literacy was found after peer education (Nafisah et al, 2023).…”
Section: Schedule and Stages Of Implementationmentioning
confidence: 53%
“…Anemia education programs in Islamic boarding schools and high schools show no significant differences because both programs can improve female students' knowledge. Consistent with community services among adolescent females in Islamic boarding schools in Purwokerto, an increase in reproductive health literacy was found after peer education (Nafisah et al, 2023). The introduction of local food, food nutrients, primary and secondary processing, as well as the development of new products and innovations, are covered in the local food processing module, while the local food management module includes the selection of raw materials and types of packaging, hygiene and sanitation in food production, local food safety, marketing strategies, business models, and business management as shown in Figure 2.…”
Section: Schedule and Stages Of Implementationmentioning
confidence: 53%
“…Tingkat pendidikan telah diidentifikasi sebagai faktor penentu yang signifikan dalam pemanfaatan layanan kesehatan reproduksi, dimana pencapaian pendidikan yang lebih tinggi berkorelasi dengan peningkatan pemanfaatan layanan tersebut (Sekoni et al, 2016). Penelitian juga menunjukkan bahwa program literasi kesehatan reproduksi, seperti inisiatif pendidikan sebaya, dapat meningkatkan pengetahuan peserta tentang kesehatan reproduksi secara signifikan (Nafisah et al, 2023). Selain itu, pendidikan seksual komprehensif, yang menggabungkan strategi kesehatan dan berbasis hak, telah diakui sebagai sarana untuk memberdayakan masyarakat dan meningkatkan kesejahteraan secara keseluruhan (Gariba & Hadjez, 2022).…”
Section: Tingkat Pendidikanunclassified